Influence of Co-Firing PKS (Palm Kernel Shell) with Coal on Boiler Efficiency Combustor Type: Reciprocating Servo Grate - Tratama, Teddy; Aspiyansyah, Aspiyansyah; Harianto, Agus; Budi, Agung Prasetyo (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
Biomass fuel, recognized for its renewable and environmentally friendly characteristics, presents an attractive option for energy production. This study explores a co-firing system incorporating palm kernel shell (PKS) and coal as fuel feeds for a boiler, aiming to optimize energy production and reduce gas emissions. The influence of co-firing PKS with coal on fuel feed rate and boiler efficiency was analyzed. Boiler efficiency measurements and calculations were conducted using the indirect method. The fuels were co-fired in various ratios: 65:35, 60:40, 55:45, and 50:50 (PKS). The results show that increasing the coal ratio in the fuel blend reduces the fuel feed rate and increases boiler efficiency. The optimized co-firing ratio of PKS to coal was determined to be 60:40, achieving a maximum boiler efficiency of 55.38%.